The Influence of Self-Efficacy, Knowledge, Attitude, and Skills on the Organizational Performance of the Ministry of Transportation, Mediated by Personnel Competence, Graduates of Indonesian Aviation Higher Vocational Education - Widayat, Tri Agung; Arafah, Willy; Anggiani, Sarfilianty (International Journal of Social Service and Research, 2024)
This research delves into the impact of various factors on Organizational Performance, with a specific focus on graduates of Vocational Higher Education in Aviation in Indonesia employed as Civil Servants (ASN) within the Ministry of Transportation. The factors under scrutiny include Self-efficacy, Knowledge, Attitude, and Skill, with an exploration of their positive influence on Organizational Performance. Furthermore, the study examines how these factors contribute to Personnel Competence among these graduates and assesses the resultant effect on Organizational Performance within the Ministry of Transportation. Additionally, it investigates the mediating role of Personnel Competence in the relationship between Self Efficacy, Knowledge, Attitude, Skill, and Organizational Performance. Employing a quantitative survey method with a positivistic approach, this study utilizes Structural Equation Modeling (SEM) for data analysis. Through this methodology, the research aims to elucidate the correlation between graduate competencies and organizational tasks. The ultimate goal is to provide valuable insights into bolstering organizational performance through effective human resource development strategies within the aviation sector, thereby catering to readers unfamiliar with the topic or research methods and ensuring clarity and coherence in the language to enhance understanding.